Generation and Field Relations of Low-δ18O Silica-Undersaturated and Mildly Saturated Alkaline Magmas: a Case Study from the Fataga Group, Gran Canaria. (1st September 2022) - Cortes-Calderon, Edgar A; Ellis, Ben S; Harris, Chris; Mark, Darren F; Neukampf, Julia; Wolff, John A; Ulmer, Peter; Bachmann, Olivier
Abstract: The origins of felsic low-δ 18 O melts (< +5.5‰) are usually attributed to assimilation of high-temperature hydrothermally altered (HTHA) rocks. Very few alkaline (silica-undersaturated and/or peralkaline) examples are known. Here, we classify the Miocene Fataga Group in Gran Canaria, a silica-undersaturated to mildly saturated alkaline volcanic sequence consisting of trachytic to phonolitic extra-caldera ignimbrites and lavas, as a new low-δ 18 O felsic locality. We provide new mineral, glass, and bulk geochemical data linked to a well-constrained stratigraphy to assess the processes involved in the magma reservoir that fed the Fataga eruptions. New high-precision single crystal feldspar 40 Ar/ 39 Ar ages of the study area span 13.931 ± 0.034 Ma to 10.288 ± 0.016 Ma. Fractional crystallization at shallow depths of sanidine/anorthoclase, biotite, augite/diopside, titanite, ilmenite, and titanomagnetite is the main driving process to produce phonolitic magmas from trachytic melts. Evidence of mafic hotter recharge is not found in the field, but some units exhibit trachytic compositions characterized by positive Eu/Eu * anomalies and high Ba contents, interpreted as melts of feldspar-dominated cumulates, the solid remnants of fractional crystallization. Hence, recharge magmas halted in the crystal mush and provided the heat needed to sustain cumulate melting and volcanic activity. This cumulate signature might be lost if fractional crystallization continues before the eruption. The interplay among meteoric water, the caldera-fault system, intra-caldera ignimbrites (Mogán Group), and the Fataga magma reservoir favoured assimilation of up to ca. 30% of HTHA rocks. Such assimilation is variable through time and recorded by δ 18 Omelt values down to +4.73‰. We did not find any direct relation between assimilation and silica saturation of the Fataga volcanic deposits.